2001
DOI: 10.1038/sj.bjp.0704172
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of allergen and polycation induced cutaneous responses in the rabbit

Abstract: 1 Allergic in¯ammatory responses contribute to the symptoms of a number of diseases including atopic dermatitis, asthma and rhinitis. Cationic proteins are released from in¯ammatory cells and levels are known to be raised in disease states. 2 Using an in vivo model of acute in¯ammation, we investigated the characteristics of cutaneous responses to antigen (Alternaria tenuis, AT) and poly-L-lysine (PLL, used as a paradigm for cationic proteins). We aimed to compare the in¯ammatory pro®le of cationic polypeptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Furthermore, in asthma, increased arginase activity diverts L-arginine toward increased production of the polycations spermine, spermidine, and putrescine (4, 5, 11). Although in human peripheral blood monocytes spermine exhibits anti-inflammatory properties (12), associations between increases in polycations in the asthmatic airway mucosa and AHR/airway remodeling and inflammation (4, 5, 13) have long been apparent and ascribed to their positive charge (9). However, the cause-effect relationship remains hitherto unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in asthma, increased arginase activity diverts L-arginine toward increased production of the polycations spermine, spermidine, and putrescine (4, 5, 11). Although in human peripheral blood monocytes spermine exhibits anti-inflammatory properties (12), associations between increases in polycations in the asthmatic airway mucosa and AHR/airway remodeling and inflammation (4, 5, 13) have long been apparent and ascribed to their positive charge (9). However, the cause-effect relationship remains hitherto unexplained.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that i.d. injection of PLL causes a dose and time dependent PE and PMNA response and that the PE response is PMN independent in the rabbit (Jones et al ., 2001). Ten minute i.d.…”
Section: Resultsmentioning
confidence: 99%
“…The leukocyte pellets were combined and resuspended in 2 ml platelet poor plasma (PPP), and 10 μl taken for counting. The cell preparation was >95% neutrophils of which >95% were viable (Jones et al ., 2001). Cells were incubated at room temperature with mercaptopyridine (5 min) followed by 111 In Cl 3 (11.1 MBq, 30 min).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations